The Effectiveness of the Partnership Program Teaching Factory at SMK Negeri 2 Sangatta Utara in Improving Students' Job Readiness in the Automotive, Mining Geology, and Nautical Merchant Ship Departments - Hariyanti, Titik; Ilma, Okta Usrifatin; Sianturi, Herpina Martangi; Azainil, Azainil; Komariyah, Laili (Lembaga Riset Mutiara Akbar, 2025)
This study aims to improve the effectiveness of the teaching factory partnership program at SMK Negeri 2 Sangatta Utara in improving students' work readiness in the Automotive, Mining Geology, and Merchant Ship Nautical majors. Teaching factory is a production and service-based learning model implemented in an environment that copies the real conditions of the industrial world. The research method used is descriptive qualitative with a case study approach, which was chosen because it allows for in-depth exploration of the dynamics and context of teaching factory implementation in certain educational units. Data collection techniques were carried out through in-depth interviews with 20 students, productive teachers, and industry partners, direct observation, and documentation studies. The results of the study showed that teaching factory provides contextual learning experiences to students, strengthens technical and soft skills, and increases self-confidence in facing the world of work. Partnerships with industry also strengthen the relevance of open materials and open up job placement opportunities for graduates. However, several challenges such as limited production equipment and practice schedules still need to be overcome to optimize this program. Thus, teaching factory has proven effective as a strategy to strengthen the link and match between SMK and industry.